2SPD-012 Relative value units as a productivity score of management of oncology medication in special situations. (March 2019) - Navarrete Rouco, ME; Acin, P; Carballo, N; Conde, D; Grau, S
Abstract : Background: Relative value units (RVU) as a clinical management tool prove to be useful in measuring different pharmaceutical activities. However, little is known about RVU for the management of medication in special situations. Purpose: To measure productivity in the management, dispensation, elaboration and pharmaceutical care activity of oncology medication in special situations: expanded or early access (EA) and 'off-label' use in a pharmaceutical department by estimating RVU. Material and methods: Retrospective and observational study performed in a tertiary hospital. Data from all EA and off-label use oncology drugs requests were collected from January 2015 to February 2018 (38 months). Variables collected: active drug, kind of drug in special condition (EA/'off-label') and length of treatment. Pharmaceutical processes included: management, dispensation, elaboration and pharmaceutical care. RVU assigned to each activity have been obtained from a standardised document drawn up by the Spanish Society of Hospital Pharmacists. 1 Results: Seventy-five oncology drug requests were analysed, of which 58 (77.3%) were EA. Nivolumab nine (13%), pertuzumab/cabonzatinib seven (10%), bevazicumab/liposomal irinotecan six (9%) and trametinib/durvalumab five (7%) were the most requested. The average length of treatment was 5.9 months. Conclusion: The pharmaceutical process with the highest productivity was elaboration of cytotoxic drugs. The processing of EA vs 'off-label' in oncology means 92.4% of total management activity. Reference and/or acknowledgements: Grupo TECNO. Servicio de Farmacia Hospitalaria. Catálogo de productos y Facturación. Madrid, 2009. No conflict of interest.